Ruby Redfort feel the fear - Child, Lauren (Child, Lauren. Ruby Redfort (Series), 2016)
"When a ghostly foe begins stealing from the highest buildings in Twinford, Ruby Redfort is ready to defy death one more time to capture the bandit"--OCLC.